2021
DOI: 10.3389/fmed.2021.737602
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing of SARS-CoV-2 Strains in COVID-19 Patients From Djibouti Shows Novel Mutations and Clades Replacing Over Time

Abstract: Since the start of COVID-19 pandemic the Republic of Djibouti, in the horn of Africa, has experienced two epidemic waves of the virus between April and August 2020 and between February and May 2021. By May 2021, COVID-19 had affected 1.18% of the Djiboutian population and caused 152 deaths. Djibouti hosts several foreign military bases which makes it a potential hot-spot for the introduction of different SARS-CoV-2 strains. We genotyped fifty three viruses that have spread during the two epidemic waves. Next, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We proposed several hypotheses that could possibly account for a late emergence and lower spread of COVID-19 in African countries, including the lack of detection and reporting of COVID-19 cases, social distancing, reduced international air traffic flows, climate, the relatively young (asymptomatic cases) and rural population, the genetic polymorphism of ACE2 or other genes involved in the control of viral replication, the use of anti-malarial drugs, and, ultimately, cross-immunity conferred by other viruses circulating in Africa [ 163 ]. Subsequently, our whole genome sequencing analyzes and those of other teams showed that African populations are sensitive to the same lineages as people from other continents [ 164 , 165 , 166 ]. Several studies have shown immune reactivity to SARS-CoV-2 proteins in samples from individuals that were collected before the COVID-19 pandemic, providing definitive evidence that SARS-CoV-2 cross-reactive immune responses may be derived from pre-existing immunity against previous non-SARS-CoV-2 infections.…”
Section: Discussionmentioning
confidence: 92%
“…We proposed several hypotheses that could possibly account for a late emergence and lower spread of COVID-19 in African countries, including the lack of detection and reporting of COVID-19 cases, social distancing, reduced international air traffic flows, climate, the relatively young (asymptomatic cases) and rural population, the genetic polymorphism of ACE2 or other genes involved in the control of viral replication, the use of anti-malarial drugs, and, ultimately, cross-immunity conferred by other viruses circulating in Africa [ 163 ]. Subsequently, our whole genome sequencing analyzes and those of other teams showed that African populations are sensitive to the same lineages as people from other continents [ 164 , 165 , 166 ]. Several studies have shown immune reactivity to SARS-CoV-2 proteins in samples from individuals that were collected before the COVID-19 pandemic, providing definitive evidence that SARS-CoV-2 cross-reactive immune responses may be derived from pre-existing immunity against previous non-SARS-CoV-2 infections.…”
Section: Discussionmentioning
confidence: 92%
“…Several qPCR were performed with primers and probes designed for specific regions of the SARS-CoV-2 genome involving characteristic mutations of VOCs and other variants. Four systems discriminated the VOCs: the UK Alpha variant (B.1.1.7, clade 20I) was targeted in the ORF8 gene, the Delta variant (B.1.617.2) was targeted by mutation P681R in the spike glycoprotein, the South African Beta variant (B.1.351, clade 20H) was targeted in the nsp2 gene, the Brazil Gamma variant (P1) was targeted in the N gene ( 22 ), ( Supplementary Table 1 ). Two systems discriminated the reference strain NC_045512.2 (19A): the first targeted the RNA-dependent RNA polymerase (RdRp) gene, and the second, a spike glycoprotein fragment including 614D ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This variant rapidly spread in South-Africa, in South-Eastern Africa (Mozambique, Zambia, Botswana, Malawi, Zimbabwe) and in Europe between February 2021 and May 2021, though it was present on all continents ( 21 ). In the Republic of Djibouti, during the second wave of the pandemic, between February and May 2021, the South African variant (clade 20H) was linked with an increase in the number of severe forms of COVID-19 in patients ( 22 ). The Gamma variant (L18F, K417T, E484K, N501Y mutations) mostly spread in South America and Caribbean countries in June 2021 ( 16 , 23 ).…”
Section: Introductionmentioning
confidence: 99%